Alcohol Withdrawal Increases Protein Kinase A Activity in the Rat Inferior Colliculus. (26th September 2016) - Akinfiresoye, Luli R.; Miranda, Clive; Lovinger, David M.; N'Gouemo, Prosper
Abstract : Background: Cyclic AMP‐dependent protein kinase A (PKA) signaling is a key target for the action of alcohol and may therefore play a role in the pathophysiology of alcohol withdrawal seizures (AWSs). Here, we investigated the role of PKA activity with respect to increased seizure susceptibility in rats that were subjected to alcohol withdrawal. Methods: Adult male Sprague Dawley rats received 3 daily doses of ethanol (EtOH) (or vehicle) for 4 consecutive days. Rats were then tested for susceptibility to acoustically evoked AWSs 3, 24, and 48 hours after the last alcohol dose. In separate experiments, the inferior colliculus (IC) was collected at these same time points from rats subjected to alcohol withdrawal and control rats following alcohol withdrawal. PKA activity, catalytic C α (PKAC α ) protein, regulatory RII α (PKARII α ) protein, and RII β (PKARII β ) protein were measured in the IC. Lastly, in situ pharmacological studies were performed to evaluate whether inhibiting PKA activity in the IC suppressed AWSs. Results: In the EtOH‐treated group, AWSs were observed at the 24‐hour time point, but not at the 3‐hour or 48‐hour time points. In the IC, PKA activity was significantly higher both 3 hours (i.e., before AWS susceptibility) and 24 hours after the last alcohol dose (when AWS susceptibility peaked) than in control rats. Consistent with these findings, protein levels of the PKAC α subunit were significantly increased in the IC both 3 and 24 hours after the last alcohol dose. Lastly, in situ inhibition of PKA activity within the IC suppressed AWSs. Conclusions: The increase in PKA activity and PKAC α protein expression in the IC preceded the occurrence of AWSs, and inhibiting PKA activity within the IC suppressed acoustically evoked AWSs. Together, these findings suggest that altered PKA activity plays a key role in the pathogenesis of AWSs. Abstract : The role of cAMP‐dependent protein kinase A (PKA) signaling in the mechanisms that underlie neuronal hyperexcitability that drives alcohol withdrawal‐induced seizures (AWSs) initiated in the inferior colliculus (IC) is poorly understood. We found that PKA activity and PKAC α protein expression were increased in the IC and preceded the occurrence of AWSs, and inhibiting PKA activity within the IC suppressed AWSs. We conclude that altered PK activity in the IC plays a key role in the pathogenesis of AWSs.